THE INFLUENCE OF FINANCIAL RATIO AGAINST THE STOCK RETURNS OF BANK COMPANIES IN INDONESIAN STOCK EXCHANGE IN 2014-2017 - AJENG LAKSMI DEWANTI; YULI CHOMSATU; ENDANG MASITOH (JURNAL WIDYA GANECWARA, 2019)
The purpose of0this study was to examine the effect of financial ratios such as Return on Equity (ROE), Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT) and Price to Book Value (PBV) on stock returns on banking companies listed on the Stock Exchange in Indonesia. The number of samples in this study were 130 companies from 2014 to 2017 that had been selected0by purposive sampling method. The research method used is multiple linear regression analysis using SPSS version 22.0. The results of0this study indicate that the ROE variable partially has a positive and significant effect on stock0returns.